Advances in hyperbaric oxygen to promote immunotherapy through modulation of the tumor microenvironment - Wang, Pei; Wang, Xiao-Yan; Man, Chang-Feng; Gong, Dan-Dan; Fan, Yu (Frontiers in Oncology, 2023)
Hyperbaric oxygen therapy is a relatively safe treatment method that has been used for a long time in the clinic. It has been proven that it can enhance the sensitivity of radiotherapy and photodynamic therapy for cancer. However, there are few studies on hyperbaric oxygen and immunotherapy. In this article, we summarize that hyperbaric oxygen therapy regulates the tumor microenvironment through various pathways such as improving tumor hypoxia, targeting hypoxia-inducing factors, and generating reactive oxygen species. The change in the tumor microenvironment ultimately affects the curative effect of immunotherapy. Therefore, hyperbaric oxygen can influence immunotherapy by regulating the tumor microenvironment, providing a direction for the future development of immunotherapy.